Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-237
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Separated-Flow Transition

Abstract: The present study formulates an improved approach for analyzing separated-flow transition that differentiates between the transition process in boundary layers which are laminar at separation and those which are already transitional at separation. The paper introduces new parameters that are necessary in classifying separated-flow transition modes and in accounting for the concomitant evolution of transition in separated shear layer and the average effect of periodic separation bubble build-up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 4 publications
3
29
1
Order By: Relevance
“…He also tried to identify critical parameters for the bursting onset and showed that for the longer bubbles and low freestream turbulence, much of the flow within the bubble is laminar and Tollmien-Schlichting instabilities have been observed. The phenomenon of transition triggered by separation bubble was also described by Hatman and Wang [5] [6][7] [8]. For constant freestream conditions (turbulence intensity and adverse pressure gradient) when lowering the Reynolds number the bubble size increases.…”
Section: Introductionmentioning
confidence: 91%
“…He also tried to identify critical parameters for the bursting onset and showed that for the longer bubbles and low freestream turbulence, much of the flow within the bubble is laminar and Tollmien-Schlichting instabilities have been observed. The phenomenon of transition triggered by separation bubble was also described by Hatman and Wang [5] [6][7] [8]. For constant freestream conditions (turbulence intensity and adverse pressure gradient) when lowering the Reynolds number the bubble size increases.…”
Section: Introductionmentioning
confidence: 91%
“…It was believed that the T-S waves, triggered by the synthetic jet and enhanced by the natural instability of the base flow, effectively stopped the flow separation [12]. In the model development for boundary layer separation, Hatman and Wang assumed that the transition to turbulence in separated boundary layer be a result of the superposition of the effects of K-H instability and T-S instability [10]. The fluctuating velocity profiles in the separation zone in Figure 3 As found in our earlier studies [11], when a synthetic jet was injected in a quiescent condition (without a cross flow), the jet velocity and momentum were maximum at a forcing frequency which was equal to the resonant frequency of the membrane material of the actuator.…”
Section: Kelvin-helmholtz (K-h) Instability Is Known As a Non-viscousmentioning
confidence: 99%
“…SeeTable 1for measurement positions in x direction.The effectiveness of the synthetic jet on resisting flow separation can also be identified with the displacement thickness. According to the identification methods developed by Hatman and Wang[10], in laminar separation, the maximum displacement of the shear layer occurs at the onset of the transition, and the maximum turbulence level occurs at the first reattachment point. The boundary layer condition in the current study belongs to the laminar separation-short bubble.Figure 4(a) shows the comparison of displacement thicknesses in the conditions with the synthetic jet on and off.…”
mentioning
confidence: 99%
“…This is noteworthy, as it will be shown in Section 7.4.3 that PAKD-FP has a small suction surface separation bubble while PAKD-F does not. Previous work has shown that the existence and location of a separation bubble is dependent on the pressure gradient history of the boundary layer (Hatman and Wang, 1999;Yaras, 2001;Houtermans et al, 2004).…”
Section: Velocity Distributionsmentioning
confidence: 99%